Analysis of the opening process of the PRC's economy in the first phase of reforms (1979-1989) - Horňáková, Petra Sofia (2013)
Over the past three decades, the People 's Republic of China has witnessed a tremendous economic growth. It was enabled by the Open Door policy, which was actively enforced since 1979. This work assess the effect that particular aspect of the reform process had on the economic growth between the years 1979 and 1989. We look into the impacts and developments of FDI, which had close ties with establishment of SEZ. As it turned out, foundation of SEZ had tremendous impact on the inflow of foreign capital as well as on gaining the trust of western world. There were also big changes in the field of foreign trade - in volume and also in its structure. The structure of foreign trade grew closer to that of developed countries and developed western countries became basically the only trading partners. Modernization of the economy, increasing of the labor productivity and growth of trade resulted in an increase of the gross domestic product. Using Hodrick-Prescott filter has been verifed growth of the whole potential of Chinese economy, not only growth real GDP, which could be affected by an investment bubble caused by exaggerated enthusiasm of investors.